Overexpression of miRNA-3613-3p Enhances the Sensitivity of Triple Negative Breast Cancer to CDK4/6 Inhibitor Palbociclib - Yu, Yuanhang; Liao, Han; Xie, Rong; Zhang, Yue; Zheng, Renjing; Chen, Jianying; Zhang, Bo (Frontiers in Oncology, 2020)
Triple negative breast cancer (TNBC) is characterized by lack of expression of the estrogen and progesterone receptors and HER2, which are common therapeutic targets. CDK4/6 inhibitor Palbociclib has been approved as an anti-cancer agent for breast cancer. However, identifying biomarkers that predict the response to Palbociclib has always been a challenge for molecular targeted therapy. In this study, we identify microRNA as a hallmark in TNBC patients and explore if miR-3613-3p might serve as a tumor suppressor biomarker for triple negative breast cancer patients and if overexpression of miR-3613-3p could enhance the sensitivity of TNBC cells to Palbociclib. We show that the expression of miR3613-3p was down-regulated in TNBC tumors and cells, and the overexpression of miR-3613-3p in patients’ tumor tissues was clinically and pathologically correlated with favorable prognosis, such as smaller tumor size and the lower Ki-67. In vitro, overexpression of miR-3613-3p inhibited cell proliferation, induced G1 cell-cycle arrest, and enhanced the sensitivity of TNBC cells to Palbociclib treatment. In vivo study revealed that overexpression of miR-3613-3p inhibited TNBC tumorigenesis and exerted a significant inhibitory effect of Palbociclib on MDA-MB-231 cells. Mechanically, SMAD2 and EZH2 were found to be two direct targets of miR-3613-3p and mediate the proliferation of TNBC cells and the sensitivity of the cells to Palbociclib through inducing cellular senescence. Our findings suggested that miR-3613-3p acts as a cancer-suppressor miRNA in TNBC. Moreover, our study showed that miR-3613-3p might be used as a predictive biomarker for the response of TNBC to Palbociclib.